2015
DOI: 10.17159/2410-972x/2015/v25n1a4
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of atmospheric black carbon in the Vaal Triangle and Highveld Priority Areas

Abstract: Atmospheric black carbon is an important atmospheric pollutant; it has impacts on human health and a strong climate impact. Black carbon particles are functionally defined by their optical properties (viz. characteristics in light absorption). As a result, black carbon particles are derived from a wide range of sources, but are largely the result of incomplete combustion processes. In order to quantify the atmospheric load of black carbon particles, multi angle absorption photometer (MAAP) instruments have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
3
6
0
Order By: Relevance
“…Limited studies are available on lightabsorbing aerosols, particularly in areas impacted by residential solid-fuel combustion. In a study at multiple sites in the Vaal Triangle Airshed Priority Area and Highveld Priority Area in South Africa, Feig et al (2015) found that seasonal cycle was similar to that of general domestic solidfuel combustion particularly in low-income settlements that use solid-fuel for domestic purposes. The significance of local anthropogenic-related sources to the burden of BC was indicated by the bimodal diurnal pattern of measured BC with peaks in the mornings and evenings, correlating with the times when domestic burning and traffic emissions was more prominent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited studies are available on lightabsorbing aerosols, particularly in areas impacted by residential solid-fuel combustion. In a study at multiple sites in the Vaal Triangle Airshed Priority Area and Highveld Priority Area in South Africa, Feig et al (2015) found that seasonal cycle was similar to that of general domestic solidfuel combustion particularly in low-income settlements that use solid-fuel for domestic purposes. The significance of local anthropogenic-related sources to the burden of BC was indicated by the bimodal diurnal pattern of measured BC with peaks in the mornings and evenings, correlating with the times when domestic burning and traffic emissions was more prominent.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of adequate information on light-absorbing particles contributes to the uncertainties associated with comprehensive assessment of the impacts of aerosols on human health and climate (Bergstrom et al, 2007;Wu et al, 2009;Yan et al, 2017;Laakso et al, 2012;Vakkari et al, 2014;Maritz et al, 2015;Maritz, 2019). Efforts to understand aerosol properties are applied increasingly worldwide (for example, Yang et al, 2009;Chakrabatry et al, 2010;Favez et al, 2010;Gadhavi and Jayaraman, 2010;Segura et al 2014;Tiwari et al, 2016, Dumka et al, 2018 but there is still limited work done on light-absorbing aerosol fractions in southern Africa (for example, Laakso et al, 2012;Vakkari et al, 2014;Feig et al, 2015;Maritz et al, 2015;Chiloane et al, 2017;Maritz, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Results in figure 2 and table 2 below illustrate that most of the stations have more exceedances per year than the NAAQS limit of 4, with Kliprivier having the most amount of exceedances over the last 10 years. For the past five years the Diepkloof monitoring station has been compliant with the NAAQS limit as the sources of emissions at Diepkloof are from household combustion and very limited industrial activities (Feig et al, 2015). The NAAQS annual mean concentration limit for PM 2.5 is 25µgm -3 .…”
Section: Resultsmentioning
confidence: 99%
“…Diepkloof had 6 exceedances years during 2007-2017 for PM 2.5 annual average concentration in comparison to NAAQS limit for annual average concentration. At Diepkloof there are not many heavy industries and no major mines in close proximity (Feig et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation